Beyond spirituality to broader social change : a qualitative analysis of the development role of the christian church in a rural community in Limpopo province - Thebe, Vusilizwe (University of Pretoria, 2022)
Dissertation (MSocSci (Development Studies))--University of Pretoria, 2022.